PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING PADA MATERI DIMENSI TIGA DI SMKN 3 PONTIANAK - Barita Riana Sitorus; Halini Halini; Silvia Sayu (Universitas Tanjungpura, 2019)
AbstractThe thesis entitled The Implementation of Contextual Teaching and Learning Model in Geometry Subject in SMK Negeri 3 Pontianak aimed to determine the effectiveness of the Contextual Teaching and Learning (CTL) model in geometry subject in SMK Negeri 3 Pontianak. The research method used was pre-experimental design with the research design used was one shot study design. The study sample was 30 students from class XII AP 1 of SMK Negeri 3 Pontianak. From the results of the study it showed that the teacher’s ability (researchers) in implementing learning with the CTL model was very good with an average of 3.84, the percentage of student’s learning activity based on groups was classified as very active with an average of 96.73% and student respond positively to learning with a percentage of 81.17%. 53% of students reached proficiency levels in study. It can be concluded that learning using the Contextual Teaching and Learning model is not effective for 12th grade geometry subject in SMK Negeri 3 Pontianak. Keywords: Contextual Teaching and Learning Model, Geometry Subject, Learning Effectiveness